2020
DOI: 10.1007/s12103-020-09534-4
|View full text |Cite
|
Sign up to set email alerts
|

Cybercrime in America amid COVID-19: the Initial Results from a Natural Experiment

Abstract: The COVID-19 pandemic has radically altered life, killing hundreds of thousands of people and leading many countries to issue "stay-at-home" orders to contain the virus's spread. Based on insights from routine activity theory (Cohen & Felson 1979), it is likely that COVID-19 will influence victimization rates as people alter their routines and spend more time at home and less time in public. Yet, the pandemic may affect victimization differently depending on the type of crime as street crimes appear to be decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 45 publications
0
50
0
2
Order By: Relevance
“…Many have noted that most street crimes have decreased during lockdown due to reduced opportunities for physical convergence between offenders and targets (Ashby 2020a;Mohler et al 2020), as has also been shown in the UK (see Figure 1), while domestic abuse may increase since perpetrators and victims are required to remain confined in the same space for long periods of time (Piquero et al 2020). Some argue that the massive move towards home working and online shopping during the outbreak may also contribute to a displacement of crime opportunities from offline to online environments (Collier et al 2020;Hawdon et al 2020;Payne 2020;Payne et al 2020). In other words, as persons spend more time connected to the Internet, and less time on the streets, opportunities for street violent and property crimes decrease while Internet crimes may increase (Miró-Llinares and Moneva 2019).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Many have noted that most street crimes have decreased during lockdown due to reduced opportunities for physical convergence between offenders and targets (Ashby 2020a;Mohler et al 2020), as has also been shown in the UK (see Figure 1), while domestic abuse may increase since perpetrators and victims are required to remain confined in the same space for long periods of time (Piquero et al 2020). Some argue that the massive move towards home working and online shopping during the outbreak may also contribute to a displacement of crime opportunities from offline to online environments (Collier et al 2020;Hawdon et al 2020;Payne 2020;Payne et al 2020). In other words, as persons spend more time connected to the Internet, and less time on the streets, opportunities for street violent and property crimes decrease while Internet crimes may increase (Miró-Llinares and Moneva 2019).…”
Section: Introductionmentioning
confidence: 89%
“…For instance, many use their personal computers to access business information, web conferencing substitutes in-person meetings, online shopping grows as a way to purchase products and services, and businesses remain empty for weeks while households are occupied most of the time. If the pandemic-related lockdown measures are multiplying the use of computer networks for business and leisure, and the number of e-commerce users is growing rapidly (Office for National Statistics 2020a), it is also likely that new opportunities for the convergence described by RAA will arise on the Internet (Hawdon et al 2020). In this sense, Payne (2020) analysed data from the US Federal Trade Commission and observed that reports of most types of fraud increased during the first months of 2020 compared to the same period in 2019; Lallie et al (2020) noted that known cyber-attacks reported globally increased during the outbreak; and Collier et al (2020) observed an increase in denial of service attacks in the UK.…”
Section: Lockdown Routine Activities and Cybercrimementioning
confidence: 99%
See 1 more Smart Citation
“…In recent months, studies have emerged internationally which have helped establish the extent to which crime (or police calls for service) during lockdowns have deviated from expected trends (see Table 1). These contributions have largely featured case study sites in the United States, including San Francisco and Oakland (Shayegh & Malpede, 2020), Los Angeles (Campedelli et al, 2020;Mohler et al, 2020), Detroit (Felson et al, 2020), Indianapolis (Mohler et al, 2020), Dallas (Piquero et al, 2020) and Chicago (Bullinger et al, 2020), although a small number of these have have examined multiple cities simultaneously (Ashby, 2020b(Ashby, , 2020a and nationwide (Hawdon et al, 2020). Although the focus has been in the United States, studies have also been conducted in the United Kingdom (Buil-Gil, Miro-Llinares, et al, 2020;Halford et al, 2020), Australia (Payne & Morgan, 2020a, 2020b, Sweden (Gerell et al, 2020) and Canada (Hodgkinson & Andresen, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While increases in crime have also been reported for cybercrime (Buil-Gil 2020;Hakak et al 2020), including online fraud (e.g. Naidoo 2020; Cimpanu 2020), malware (Brumfield 2020), hacking and phishing (Muncaster 2020;Kumaran and Lugani 2020), Hawdon, Parti and Dearden (2020) report that cybercrime remained unchanged despite the swift change in routine activities. However, data on such crimes is more elusive and analyses-at least in the academic and open source literature-less complete than for more traditional crimes such as those discussed above.…”
Section: Introductionmentioning
confidence: 99%